2021
DOI: 10.21203/rs.3.rs-294601/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Purinergic signaling mediates neuroglial interactions to generate sighs

Abstract: Sighs prevent the collapse of alveoli in the lungs, initiate arousal under hypoxic conditions, and even express sadness and relief. Sighs are periodically superimposed on normal breaths, known as eupnea. Implicated in the generation of these rhythmic behaviors is the preBötzinger complex (preBötC)1. Yet how this small microcircuit can produce two rhythms with strikingly different periodicities remains unresolved. Our computational simulations predict that sighs are generated by the coincidence of two temporall… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…S1C). A parallel experiment employed the highly selective P2Y 1 antagonist MRS2279 because recent evidence in preprint form purports that gliotransmission specifically via P2Y 1 receptors is obligatory for sigh rhythmogenesis in vitro (17). Bath-applied 20 μM MRS2279 had no effect on either inspiratory or sigh rhythm (inspiratory rhythm: 0.20 ± 0.04 Hz in control vs. 0.26 ± 0.06 Hz in MRS2279, p = 0.13; sigh rhythm: 0.86 ± 0.45 min -1 in control vs. 0.61 ± 0.28 min -1 in MRS2279, p = 0.26) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…S1C). A parallel experiment employed the highly selective P2Y 1 antagonist MRS2279 because recent evidence in preprint form purports that gliotransmission specifically via P2Y 1 receptors is obligatory for sigh rhythmogenesis in vitro (17). Bath-applied 20 μM MRS2279 had no effect on either inspiratory or sigh rhythm (inspiratory rhythm: 0.20 ± 0.04 Hz in control vs. 0.26 ± 0.06 Hz in MRS2279, p = 0.13; sigh rhythm: 0.86 ± 0.45 min -1 in control vs. 0.61 ± 0.28 min -1 in MRS2279, p = 0.26) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We conclude that glia and gliotransmission are not mandatory for sigh rhythmogenesis because attenuating purinergic P2Y signaling, the dominant means by which astrocytes interact with preBötC neurons (3032), did not preclude or modify sigh rhythmogenesis. A recent report in preprint form showed that blocking gliotransmission at P2Y 1 receptors stops the sigh rhythm in vitro but does not stop sighs in adult mice (17). Our conclusion is not incompatible – purinergic gliotransmission is ultimately unnecessary for sigh behavior – but our data in vitro are incongruous.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, regarding inspiration, intracellular Ca 2+ signaling in the context of SOCE could recruit Ca 2+ -activated non-specific cationic current (ICAN), which profoundly contributes to inspiratory burst pattern [29][30][31] , consistent with the role of Type-2 neurons. Sigh breaths, which occur at lower frequencies but are two-fold larger in magnitude 32 are likely also to involve Ca 2+ signaling and possibly SOCE mechanisms that recruit ICAN 33 .…”
Section: Transcriptomic Differences Between Type-1 and Type-2 Neuronsmentioning
confidence: 99%